UTILIZING SNOWBALL THROWING LEARNING MODEL TO IMPROVE STUDENTS’ LEARNING OUTCOMES FOR SUB THEME AKU CINTA MEMBACA IN CLASS 4A SDN CUKIR 1 - Yasinta Nurlaila Diniyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to describe the improvement of students’ learning outcomes through the implementation of the Snowball Throwing learning model for the sub-theme “Aku Cinta Membaca” in class 4A of SDN Cukir 1. This study employed Classroom Action Research (CAR), which consisted of several stages, namely planning, action, observation, and reflection. The data were obtained from test results, observations, documentation, and interviews. The results indicated that students’ learning outcomes increased from the pre-cycle to cycle I and cycle II through the implementation of the Snowball Throwing learning model. The percentage of students’ learning completeness in the pre-cycle was 21%, which increased to 60% in cycle I and reached 100% with a high criterion in cycle II. The improvement was also reflected in the students’ average scores. In the pre-cycle, the average score was 6.73; in cycle I, it increased to 7.32; and in cycle II, it further increased to 8.87. The results of this study concluded that the implementation of the Snowball Throwing learning model generated more effective learning and improved students’ learning outcomes.